GE_GERICHTE P/10048/2020 vom 23. Dezember 2021 - GE Cour de justice (2021)
OPPOSITION TARDIVE;FICTION DE LA NOTIFICATION;CHANGEMENT DE DOMICILE;NULLITÉ;DÉFENSE D'OFFICE | CPP.354; CPP.85.al4; CPP.87; CPP.132